A Pilot Study to Evaluate the Dietary Intake of Adults Attending a Food Allergy Clinic, and Compare the Results Against the Final Diagnostic Outcome - Skypala, Isabel J.; Taylor, Cecile F.; Pallister, Anthony; Scadding, Guy W. (Frontiers in Allergy, 2021)
Background The impact of poor diet on growth and development in children with a food allergy is well recognized and researched. Food allergy is an increasing problem in adults, as are food intolerances. Another issue is the rising number of individuals adopting a vegetarian or vegan lifestyle. Studies evaluating the diet of adolescents and adults with food allergy against controls suggest their dietary intakes are similar. We wished to evaluate all patients attending a food allergy clinic to determine whether there were dietary and nutritional differences between those with a food allergy or a food intolerance. Methods All adults newly referred to a secondary care food allergy clinic in a UK hospital, in a one-month period, were included in the study. Prior to their appointment, those who consented to take part had their height and weight documented and an assessment made of their habitual food intake. Their subsequent diagnosis was reviewed, and results for those with a confirmed diagnosis of food allergy were compared to those with a food intolerance or where the cause of symptoms was unknown. Results Thirty subjects were recruited, with full results available for 29 subjects, 15 of whom (52%) were diagnosed with a new/existing food allergy (FA). For the whole cohort, dietary intake was sufficient for protein, and most vitamins and minerals, whereas energy, carbohydrate, unsaturated fat and fiber intakes were well below the reference range. Those with a FA had lower intakes of iron, zinc and vitamin B12 compared to those with no FA. In addition, iron and energy intakes were depleted in those avoiding nuts, and wheat avoidance was linked to a lower intake of riboflavin. Conclusion The results from this small exploratory study suggest that whilst the majority of nutrients in the diet are sufficient in adults presenting to the food allergy clinic, intakes of energy and fiber may be below the reference range. Those with a food allergy are more likely to have a reduced intake of iron, zinc and vitamin B12. As others have demonstrated, the exclusion of specific food groups can also affect nutritional intakes.